1993
DOI: 10.1073/pnas.90.8.3626
|View full text |Cite
|
Sign up to set email alerts
|

Male-specific expression of mouse sex-limited protein requires growth hormone, not testosterone.

Abstract: Sex-limited protein (Slp), an isoform of mouse complement component C4, is expressed predominantly in liver and nearly exclusively in sexually mature males or testosterone-treated females. It is encoded by a gene (C4-Slp) whose hormonal dependence has been attributed to an androgen-responsive transcriptional enhancer introduced accidentally, alongside the C4-Slp promoter, in the guise of the 5' long terminal repeat of an ancient retrovirus. We demonstrate that the pronounced rise of C4-Slp mRNA promoted by and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…Intriguingly, however, the human CRP gene is not sexually dimorphic in humans. A possible answer to this paradox lies in the fact that testosterone produces pulses of high growth hormone release in male mice (12), resulting in mean levels in serum twice those observed in females (22). Growth hormone has been shown to be able to upregulate the human CRP gene in transgenic mice (26).…”
Section: Vol 11 2004mentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, however, the human CRP gene is not sexually dimorphic in humans. A possible answer to this paradox lies in the fact that testosterone produces pulses of high growth hormone release in male mice (12), resulting in mean levels in serum twice those observed in females (22). Growth hormone has been shown to be able to upregulate the human CRP gene in transgenic mice (26).…”
Section: Vol 11 2004mentioning
confidence: 99%
“…Since that study, the transcription factor STAT5 has emerged as an important transducer of the pulsatile growth hormone secretion pattern seen in male rodents into sex-specific patterns of liver gene expression (11,14,24). Also, binding of STAT5 to the promoter of the murine Sex-limited protein (slp) gene, which is known to be regulated indirectly by testosterone, via its effects on growth hormone (12), results in male-specific transcription of the gene (32). In addition, Feldman et al (6) have shown that GM-CSF is involved in the activation of STAT5, thereby providing another mechanism whereby GM-CSF overexpression in male GM-CSF transgenic mice might lead to the generation of a positive feedback loop, upregulating the CRP promoter and producing more GM-CSF.…”
Section: Vol 11 2004mentioning
confidence: 99%
“…Slp is normally expressed only in adult male mice, where it responds to the positive effects of pulsatile GH stimulation (Georgatsou et al 1993). Recessive rsl mutant alleles have arisen in populations of inbred mice and result in expression of Slp in female mice at 3 wk of age .…”
Section: Rsl a Regulator Of Sex Limitationmentioning
confidence: 99%
“…In the liver, the major source of Slp, the difference in expression levels of the protein in males and females is due to nuclear factors acting at the transcriptional stage (16). Full expression of Slp in males occurs only after puberty and is dependent upon the presence of testosterone, androgen receptors, and an adult male pattern of growth hormone release (16,17).Due to an apparent tandem duplication, Slp and C4 form a small multigene family (18,19 Slp (24,25).The fascinating observation was made by Brown and Shreffler (26) that in four strains that do not contain hybrid Slp genes (FM, LG, NZB, and PL), the "sex-limitation" is removed in that females also express Slp (26). Expression of Slp was characterized in detail in the strain FM (Slpd); Slp is expressed only after 4 weeks of age in either sex and is expressed in males at higher levels than in females.…”
mentioning
confidence: 99%
“…Slp was found in several independent haplotypes (Slpd, Slpu, Slps, SlpP) (13,14), and it has recently been shown to have activity in a putative complement pathway (15). In the liver, the major source of Slp, the difference in expression levels of the protein in males and females is due to nuclear factors acting at the transcriptional stage (16). Full expression of Slp in males occurs only after puberty and is dependent upon the presence of testosterone, androgen receptors, and an adult male pattern of growth hormone release (16,17).…”
mentioning
confidence: 99%